Phytotoxins Produced by Pestalotiopsis Guepinii, the Causal Agent of Hazelnut Twig Blight - Türkkan, M.; Andolfi, A.; Zonno, M.C.; Erper, I.; Perrone, C.; Cimmino, A.; Vurro, M. (Mediterranean Phytopathological Union, 2011)
The main lipophilic phytotoxic metabolite was isolated from the culture filtrates of Pestalotiopsis guepinii, the fungus causing twig blight of hazelnut. The metabolite was spectroscopically identified as pestalopyrone, a pentaketide that it was originally identified as a minor toxin produced by Pestalotiopsis oenotherae. The toxic activity of pestalopyrone was compared with that of nectriapyrone, a structurally related monoterpenoid recently isolated from Phomopsis foeniculi, and that of the new dihydro-derivative of nectriapyrone. The high phytotoxic activity of nectriapyrone and its dihydro-derivative on three non host plants, showed that the double bond of the 1-methylpropenyl group at C-6 of the aromatic ring is inessential for its activity, while the much lower activity of pestalopyrone showed that the methyl group at C-3 of the same ring is an important structural feature. The high molecular weight hydrophilic phytotoxins produced by this fungus are reported for the first time.
Keywords: Monoterpenoids; Nectriapyrone; Pentaketides; Pestalopyrone; Sar